The Effect of Buddhist Fasting and Vegetarian on The Mental Health of Bodhictta Buddhist High School Students - Chandra , Chandra; Siu , Ong Cin; Lisniasari , Lisniasari; Juli , Juli (Jurnal Ners, 2023)
Health is not a temporary need, but a lifelong need that can be said to be a very valuable investment. It can be seen from the words of the Buddha that health is the greatest gift. Health is a combination of physical and mental well-being. It is not only limited to being free from physical illness, but also avoiding mental disorders. Mental health strongly correlated with productivity and physical health. Disruption in mental health or psychological condition can be experienced by anyone. A healthy mental health is a mental condition that is always in a calm, safe and peaceful state, and also avoids various mental illnesses such as low self-esteem, anxiety, fear, anxiety, and other inner tensions. Buddhist fasting (Vikalabhojana) is fasting in general, which can be interpreted as a conscious and sincere effort and action to refrain from various temptations, desires for physical and spiritual needs, and behavior, in order to obtain a simple life, towards peace of mind to achieve holiness. Vegetarian are people who for some reason no longer consume the foods made from living beings and develops a love for living beings where every creature has the right to continue to live. Vegetarians are more inclined to consume foods in the form of whole grains, vegetables, fruits, nuts, legumes and seeds. This study uses a Quasi Experiment method with a quantitative approach, with multiple regression analysis. The type of research instrument used is in the form of a closed, direct and multilevel questionnaire. The population used in this study are 160 respondents of SMA Buddhist Bodhicitta students. The sample method used was non-probability sampling with purposive sampling technique to specially select students of class XII SMA. The results of the hypothesis test for H1 buddhis, fasting shows the Sig. value of 0.001 < 0.05 and tcount 4.521 > ttable 2,145; for H2 vegetarian shows the Sig. value of 0.005 < 0.05, or tcount 3,357 > ttable 2.145; and for H3 Sig. deviation value of 0.000 < 0.05 and Fcount 29,959 > Ftable 3,74, which means that there is an influence between the independent variable and the dependent variable, either partially or simultaneously The results of this study concluded that students’ mental health can be improved through the practice of Buddhist fasting and being vegetarian either partially (individually) or simultaneously (together).